Final Draft Feasibility Study for Sea Cucumber Pasta Noodles - Gabriel, Randee Almond (College of Engineering, 2000)
This is a five-year period project study made on the feasibility of starting a new manufacturing company in the consumer-food industry. The product is a noodle produced using the same manufacturing procedures and processes as the present noodle industry, but is innovative due to its content. The addition of sea cucumber, in either fresh or powdered form, enhances the nutritive content and consistency of the noodle. This study provides an analysis of the present market of the Philippine noodle industry within the National Capital Region. Specifically, the ABC income brackets were targeted due to the product's market price of P62.50. The initial sales plan includes distribution of the 40-50 supermarkets within NCR and promotions through newspaper advertisements and supermarket booths. The maintenance of the advertising and promotions is budgeted at P500,000 in the years following the initial product launch. The market plan was determined through a demand and supply analysis of noodle production and consumption within NCR. The smallest competitor share, 0.11% was chosen as the equivalent market share of the new company. The required production volume can be met within an 8-hour, 5-day week with overtime hours required only in the first years of production. The sea cucumber noodle manufacturing plant will be leased in a warehouse located at 107 M Alvarez St., Las Piñas. A total area of 77sq m is necessary to accommodate all the equipment, tools, supplies, labor force, and office and storage space facilities. The Total Project Cost is tabulated at the end of the chapter and is estimated to be P3,173,741.53. The Organizational Analysis renders the corporate organizational form as the best alternative for the sea cucumber noodle company. The owners of the company are the stockholders who invest in the project through the purchase of shares. The company employs a total of 4 administrative staff to handle the entire management of productions. The Financial analysis justifies the monetary feasibility of the project. Two alternatives are presented regarding the funding of the venture, which has been stated at P3,173,741.53 Alternative 1 engages the assistance of a loaning institution, Development Bank of the Philippines, to shoulder 50% of the total project cost while the remaining half will be sourced from the owners. Alternative 2 solicits complete funding from the owners. Payback period, NPV and IRR for the better alternative, which is option 2, are 3 years, P103,808.29 and 18.25% respectively. These values are favorable since the investment can be paid back within the five-year period, the NPV>0 and IRR of 18.25 is greater than MARR of 15%. Concluding the project study is a section on the social profitability of the venture. Advantages such as provisions of jobs, additional income for individuals, private businesses and the government were detailed. Disadvantages such as the creation of additional waste, possible depletion of resources, and additional use of energy were also considered. The overall study concludes a favorable position in pursuing the new company.